Outcomes of the 6th International Arctic Forum “Arctic: Territory of Dialogue” — 2025 - Valery P. Zhuravel (Арктика и Север, 2025)
The article summarizes the key outcomes of the 6th International Arctic Forum (IAF, the Forum) “Arctic: Territory of Dialogue”, held in Murmansk on March 26–27, 2025. The IAF became a platform for in-ternational dialogue on such issues as development of the Northern Sea Route, enhancing investment and entrepreneurial potential in the Arctic Zone, as well as environmental, humanitarian, and cultural cooperation. The Forum primarily focused on discussions of the state policy in the Arctic Zone of the Russian Federation (AZRF), aimed at the comprehensive development of the Far North and improving the well-being of the region’s residents.